A Population-Based Study of the Incidence and Case Fatality of Intracerebral Hemorrhage of Undetermined Etiology - Qureshi, Adnan I. (J Vasc Interv Neurol, 2015)
BACKGROUND: There is a paucity of reliable recent data regarding epidemiology of intracerebral hemorrhage (ICH) of undetermined etiology in population-based studies. OBJECTIVES: To determine the incidence and case fatality of ICH of undetermined etiology using a population-based design. METHODS: Medical records and neuroimaging data of all patients with ICH from Stearns and Benton Counties, Minnesota, between June 1st, 2012 and June 30th, 2014 were reviewed. Patients with a first-time diagnosis of ICH were categorized as of undetermined etiology if ICH was without features typical of hypertensive etiology with normal or no magnetic resonance imaging (MRI)/angiograms. We calculated the incidences of [1] probable and possible hypertensive ICH; [2] related to arteriovenous malformation, cavernous malformation, or aneurysmal rupture (angiographic or MRI diagnoses); [3] secondary to anticoagulation; and [4] of undetermined etiology adjusted for age and sex based on the 2010 US census. RESULTS: Of the 50 identified ICHs among 136,654 resident populations, seven were true incident cases of ICH of undetermined etiology in this population-based study. The age- and sex-adjusted incidence of ICH of undetermined etiology was 2.6 [95% confidence interval (CI) 0.7–4.9] per 100, 000 person-years, which was lower than probable and possible hypertensive ICH incidence of 12.8 [95% CI 8.4–17.2] per 100,000 person-years. The age-adjusted case fatality rate at 1 month was 8.14 and 0.4 per 100,000 persons for probable and possible hypertensive ICHs and ICHs of undetermined etiology, respectively. CONCLUSIONS: Our results should prompt further studies into identification of causes in ICH patients presently classified as ICH of undetermined etiology to reduce the incidence and case fatality of such ICHs.